A Comparison between Attitudes and Knowledge Towards Fast-Food and Probiotics of Undergraduates - Cebirbay, Muhammet Ali; Ekinoğlu, Ezgi (Universitas Muhammadiyah Yogyakarta, 2024)
Consumption of fast-food is increasing rapidly, whereas fast-food does not provide enough nutrients. Probiotics contribute to optimal nutrition and health benefits. This study aims to evaluate the consumption frequency, habits, and knowledge regarding fast-food and probiotics among undergraduates. We used a face-to-face interview method to obtain the data from 405 undergraduates aged 18-24 studying in Konya, Turkey. There were 46.9% of males and 53.1% of females, with an average Body Mass Index (BMI) of 22.3±0.168 kg/m2. A difference was detected in BMI according to gender (p 0.000). There were 84% of the students consuming at least one fast food a day, and 58.5% consumed probiotics daily. Statistically, there was no significance between the frequency of fast-food (p 0.456) and probiotic (p 0.680) consumption for BMI. The fast-food knowledge scores differ according to BMI (p 0.004). Probiotic knowledge scores of the overweight and obese group were lower than the other groups. A negative correlation between fast-food knowledge and BMI was (R2 - 0.011). A positive correlation between probiotic knowledge and BMI was (R2 0.034). Undergraduates consumed fast-food at high frequency, and they also know about probiotics. Nevertheless, the level of knowledge about both fast food and probiotics should be increased.